Integrated crop-livestock systems program with special reference to rice field and beef cattle is a potential alternative to support the development of agriculture sector in Indonesia. The implementation on this integrated program was to enhance rice production and productivity through a system involving beef cattle with its goal on increasing farmers’ income. The impact of integrated crop- livestock systems program to household economy farmers was studied in order to identify factors influenc - Atien Priyanti; Bonar M. Sinaga; Yusman Syaukat; Sri Utami Kuntjoro (Forum Pasca Sarjana, 2008)
Integrated crop-livestock systems program with special reference to rice field and beef cattle is a potential alternative to support the development of agriculture sector in Indonesia.  The implementation on this integrated program was to enhance rice production and productivity through a system involving beef cattle with its goal on increasing farmers’ income.  The impact of integrated crop- livestock systems program to household economy farmers was studied in order to identify factors influencing behavior of farmer’s decision-making along with its interrelation between factors.  Impact of changes due to the external policy options was also assessed and farmer’s characteristics were described descriptively.  Five districts in the province of DIY, Central Java and East Java with 274 farmers were purposively used in the study. Simultaneous equations model with two SLS method was used to estimate the parameter, followed by the non-linear simulation approach.  The results show that most of the explanatory variables significantly affected to its endogenous variables.  Rice production is responsive to harvested land area which influenced by its volume of input rice derived demand.  The volume of its input derived demand also influences cattle and compost production.  Family labor utilization for rice and cattle production and their time allocation on non-farm and off farm jobs are related to each other. Input price of rice and live cattle are affected to their derived demand function.  Rice consumption is responsive to its price which the lower the price, the higher its consumption.  Credit on crops farm that has to be paid by farmers is also responsive and positively related to its commercial credit rate.  Effect of a 10 percent increase on output and input price of production rice, cattle and compost will increase their production; hence will also increase farmers’ income and the expenditures. This will apply to farmers that involved in a program of integrated crop-livestock systems.  On the other hand, alternative policy of combination between a 10 percent increase of output price along with 5 percent increase on its input price yield in the increasing production for farmers that are not involved in the crop-livestock systems program, hence will also increase the income.   Key words: household economics, simulation analysis, crop-livestock systems